Sex-specific additive genetic variances and correlations for fitness in a song sparrow (Melospiza melodia) population subject to natural immigration and inbreeding - Wolak, Matthew E.; Arcese, Peter; Keller, Lukas F.; Nietlisbach, Pirmin; Reid, Jane M. (Evolution, 2018)
Quantifying sex-specific additive genetic variance (VA) in fitness, and the cross-sex genetic correlation (rA), is prerequisite to predicting evolutionary dynamics and the magnitude of sexual conflict. Further, quantifying VA and rA in underlying fitness components, and genetic consequences of immigration and resulting gene flow, is required to identify mechanisms that maintain VA in fitness. However, these key parameters have rarely been estimated in wild populations experiencing natural environmental variation and immigration. We used comprehensive pedigree and life-history data from song sparrows (Melospiza melodia) to estimate VA and rA in sex-specific fitness and underlying fitness components, and to estimate additive genetic effects of immigrants alongside inbreeding depression. We found evidence of substantial VA in female and male fitness, with a moderate positive crosssex rA. There was also substantial VA in male but not female adult reproductive success, and moderate VA in juvenile survival but not adult annual survival. Immigrants introduced alleles with negative additive genetic effects on local fitness, potentially reducing population mean fitness through migration load, but alleviating expression of inbreeding depression. Our results show that VA for fitness can be maintained in the wild, and be broadly concordant between the sexes despite marked sex-specific VA in reproductive success.